Usability Dimensions for Content-Orientation Techniques in Multi-Touch Tabletop Displays: An Overview - Madni, T.M. (Association for Computing Machinery, Inc, 2016)
In recent years, the use of multi-Touch tabletop display applications have greatly increased in different domains. These systems support various content-orientation techniques to perform the simultaneous multi-user multi-Touch interaction to access digital contents directly in a natural way. It is reported that existing techniques still have limited usability and user experience while performing the co-located collaborative tasks. However, it is still unclear what core usability dimensions need to be considered to assess the performance of these techniques using the different tabletop applications. Keeping in view this issue, this study aims to identify and select the core usability dimensions based on a literature review method. Based on the findings, a usability model is proposed that include three core dimensions i.e. effectiveness, efficiency, and satisfaction. The usability model also highlights the tabletop technologies, user characteristics, tasks, and contexts. It can be useful for interaction designers to empirically evaluate the content-orientation techniques using the different tabletop applications and to improve the collaboration design for the tabletop displays. Â© 2016 ACM.